Problematic issues of endoscopic biliary stenting - A. I. Dronov; I. L. Nastashenko; Yu. P. Bakunets; P. P. Bakunets; L. V. Levchenko (Клінічна хірургія)
Objective. To study the results of endoscopic biliary stenting (EBS) for biliary obstruction of various genesis to determine the problematic issues of the procedure and possibility of its efficacy raising.